Parametric analysis and optimization of a novel cascade compression-absorption refrigeration system integrated with a flash tank and a reheater - Md Walid Faruque; Yasin Khan; Mahdi Hafiz Nabil; M Monjurul Ehsan (Results in Engineering, 2023)
This article presents a novel cascade configuration for a compression absorption refrigeration system by combing a single effect absorption cycle with a reheater at the higher temperature circuit (HTC) and a modified vapor compression cycle with the flash tank at the lower temperature circuit (LTC). The proposed refrigeration system is investigated by the energy and exergy method, parametric analysis, and optimization by genetic algorithm for two different refrigerant pairs. At the LTC, the R41 refrigerant pair is employed whereas, lithium bromide solution (LiBr/H2O) and ammonia solution (NH3/H2O) are employed at the HTC. A detailed energy and exergy analysis is performed between the conventional and novel systems to illustrate the improvement achieved by the proposed system. Results suggest that at an evaporator temperature of −35 °C, using the combination of R41 and LiBr/H2O, the proposed system is capable to achieve 15.39% higher COP and exergetic efficiency than the conventional cascade absorption cycle. Furthermore, by employing R41-NH3/H2O combination under identical working conditions, the proposed system has achieved 18.49% higher COP and exergy efficiency than the conventional system. Additionally, a comparative parametric analysis between the two refrigerant pairs in the proposed system is conducted. The analysis suggests that R41-LiBr/H2O refrigerant pair has a significant advantage over the R41-NH3/H2O refrigerant pair. Lastly, the optimization of the proposed system is conducted by implementing the genetic algorithm to determine the optimal operating conditions for maximum COP and exergy efficiency.